2009
DOI: 10.1093/jhered/esp117
|View full text |Cite
|
Sign up to set email alerts
|

The Potential for Gene Flow in a Dependent Lineage System of a Harvester Ant: Fair Meiosis in the F1 Generation

Abstract: We investigated the potential for gene flow in a dependent lineage (DL) system of the harvester ant Pogonomyrmex. Each DL system is composed of 2 reproductively isolated lineages that are locked in an obligate mutualism. The genetic components that produce the worker phenotype are acquired by hybridizing with the partner lineage. In the mating flight, queens of both lineages mate with multiple males from each lineage. During colony growth and reproduction, eggs fertilized by partner-lineage sperm produce F(1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Fortunately, three previous studies have confirmed that the GCD phenotype maps onto just two discrete and apparently monophyletic clades in mtDNA phylogenies constructed from cox1 sequences (Helms Cahan and Keller 2003;Anderson et al 2006;Schwander et al 2007a). Moreover, these and other studies have repeatedly found that J and H lineages are reproductively isolated from each other and from ECD P. barbatus and P. rugosus (Helms Cahan and Keller 2003;Anderson et al 2006;Helms Cahan et al 2006;Schwander et al 2007aSchwander et al , 2007bCurry et al 2010;Sirvi€ o et al 2010). To the extent that this pattern is maintained across a broader geographic range, it is possible to define samples as derived from either a GCD or ECD clade based on phylogenetic analyses.…”
Section: Inferring Caste Determination Phenotype In New Populationsmentioning
confidence: 79%
See 1 more Smart Citation
“…Fortunately, three previous studies have confirmed that the GCD phenotype maps onto just two discrete and apparently monophyletic clades in mtDNA phylogenies constructed from cox1 sequences (Helms Cahan and Keller 2003;Anderson et al 2006;Schwander et al 2007a). Moreover, these and other studies have repeatedly found that J and H lineages are reproductively isolated from each other and from ECD P. barbatus and P. rugosus (Helms Cahan and Keller 2003;Anderson et al 2006;Helms Cahan et al 2006;Schwander et al 2007aSchwander et al , 2007bCurry et al 2010;Sirvi€ o et al 2010). To the extent that this pattern is maintained across a broader geographic range, it is possible to define samples as derived from either a GCD or ECD clade based on phylogenetic analyses.…”
Section: Inferring Caste Determination Phenotype In New Populationsmentioning
confidence: 79%
“…; Curry et al. ; Sirviö et al ). To the extent that this pattern is maintained across a broader geographic range, it is possible to define samples as derived from either a GCD or ECD clade based on phylogenetic analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Such males could father new hybrid queens, a situation that may lead ultimately to offspring with introgressed mitochondria. Both hybrid queens and hybrid males occur in Pogonomyrmex ants [18]. Nevertheless, interlineage hybrid queens of Pogonomyrmex are known to have reduced fitness, if any [17].…”
Section: Discussionmentioning
confidence: 99%
“…Queens that only mate with males of different lineage fail to produce new queens, while queens that only mate with males of their own lineage fail to produce workers and the colony is therefore not viable. Understanding the origin and maintenance of this unique system requiring three different mating partners has attracted considerable interest (Anderson et al 2006(Anderson et al , 2008Linksvayer et al 2006;Schwander et al 2006Schwander et al , 2007aVolny et al 2006;Yamauchi & Yamamura 2006;Curry et al 2009;Sirvi€ o et al 2010;Suni & Gordon 2010;Gordon et al 2013;Mott et al 2015). However, no new cases have been found since its discovery (Julian et al 2002).…”
Section: Introductionmentioning
confidence: 99%